Characterization of time-consistent sets of measures in finite trees - Monika Bier (Bielefeld University, Institute of Mathematical Economics (IMW), 2010)
In this paper we give an alternative characterization for time-consistent sets of measures in a discrete setting. For each measure P in a time-consistent set Ρ we get a distinct set of predictable processes which in return decribe the P uniquely. This implies we get a one-to-one correspondence between time-consistent sets of measures and sets of predictable processes with specific features.
urn:nbn:de:hbz:361-17050
Keywords: D81; 330; Multiple Priors; Time-Consistency; Ambiguity; Uncertainty Aversion; Entscheidung bei Unsicherheit; Risikoaversion; Erwartungsnutzen; Zeitkonsistenz; Theorie